2007
DOI: 10.2337/dc07-0589
|View full text |Cite
|
Sign up to set email alerts
|

Pramlintide Improved Glycemic Control and Reduced Weight in Patients With Type 2 Diabetes Using Basal Insulin

Abstract: OBJECTIVE -To assess the efficacy and safety of pramlintide in patients with type 2 diabetes suboptimally controlled with basal insulin.RESEARCH DESIGN AND METHODS -In a 16-week, double-blind, placebocontrolled study, 212 patients using insulin glargine with or without oral antidiabetes agents (OAs) were randomized to addition of pramlintide (60 or 120 g b.i.d./t.i.d.) or placebo. Insulin glargine was adjusted to target a fasting plasma glucose concentration of 70 -100 mg/dl. One coprimary end point was the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 23 publications
1
111
0
1
Order By: Relevance
“…It is administered subcutaneously before meals and slows gastric emptying, inhibits glucagon production in a glucose-dependent fashion, and predominantly decreases postprandial glucose excursions [33]. In clinical studies, HbA 1c has been decreased by 0.5-0.7 percentage points [82]. The major clinical side effects of this drug are gastrointestinal in nature.…”
Section: Medicationsmentioning
confidence: 99%
“…It is administered subcutaneously before meals and slows gastric emptying, inhibits glucagon production in a glucose-dependent fashion, and predominantly decreases postprandial glucose excursions [33]. In clinical studies, HbA 1c has been decreased by 0.5-0.7 percentage points [82]. The major clinical side effects of this drug are gastrointestinal in nature.…”
Section: Medicationsmentioning
confidence: 99%
“…Our searches identifi ed 166 citations; of these, 7 randomized controlled trials (RCTs), [5][6][7][8][9][10][11] 3 companion articles, [12][13][14] and 4 pooled analyses [15][16][17][18] fulfi lled inclusion criteria. We also identifi ed 2 unpublished trials (study #137-117 and #137-123) from the FDA medical and statistical reviews.…”
Section: Resultsmentioning
confidence: 99%
“…A 16 week study of pramlintide vs placebo added to therapy in T2DM patients treated with basal insulin with or without oral agents showed that pramlintide resulted in a greater A1C reduction (−0.7 % vs −0.36 % on placebo) and significant weight loss (−1.6 kg vs +0.7 kg on placebo) [70]. In a 6 month study where T2DM patients with inadequate control on basal insulin with or without oral agents were randomized to the addition of mealtime insulin vs pramlintide, patients on pramlintide maintained weight while patients on mealtime insulin gained an average of +4.7 kg, with similar improvements in glycemic control in each group (−1.1 % and −1.3 % in the pramlintide and mealtime insulin groups, respectively) [71].…”
Section: Pramlintidementioning
confidence: 99%